Hubungan Kelelahan Dengan Kejadian Depresi Pada Mahasiswa Kedokteran Semester 7 di Universitas Palangka Raya - Martha Furi, Lewi; Nuryagus Siringo, Yulinar; Pradnya Paramita, Parameswari; Br. Surbakti, Ranintha (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Fatigue can be defined as a feeling of lack of energy and difficulty in initiating or maintaining spontaneous activities.  Fatigue is a growing problem among medical students. A common reason for fatigue in medical students is excessive academic workload. In recent years, fatigue has been linked to stress which can lead to depression. Therefore, this study aims to examine the relationship between fatigue and the incidence of depression in 7th semester medical students at Palangkaraya University. This research is an observational study with a cross sectional research design. which data were taken using a questionnaire from 140 respondents using purposive sampling technique. Statistical analysis using Spearman. The results of statistical analysis showed that of 140 respondents with an age range of 20 – 23 years, 82 respondents (58.57%) experienced significant fatigue. There were 93 respondents (66.43%) experiencing minimal depression, 24 respondents (17.14%) experiencing mild depression, 16 respondents (11.43%) experiencing moderate depression and 7 respondents (5%) experiencing severe depression. From the results of the hypothesis test, it was found that there was a relationship between fatigue and the incidence of depression with a value of p = 0.001. This research shows there is a statistically significant relationship between fatigue and depression.